Pengaruh Keahlian Auditor Eksternal terhadap Pengungkapan Risiko Iklim dalam Laporan Keuangan di Perusahaan Kelapa Sawit - Leonardo, Garrant; Salim, Susanto (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of external auditor expertise on the level of climate risk disclosure in the financial statements of palm oil companies in Indonesia. The research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports of palm oil companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The population of this study consists of all palm oil companies listed on the Indonesia Stock Exchange, while the sample was determined using purposive sampling based on several criteria: companies that publish sustainability reports, financial statements audited by external auditors, and the availability of information regarding auditor expertise. The independent variable in this study is external auditor expertise, measured through professional certification and work experience, while the dependent variable is the level of climate risk disclosure measured using indicators aligned with the TCFD and PSPK 2 frameworks. Data analysis was conducted using multiple linear regression after performing classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that external auditor expertise has a positive and significant effect on the level of climate risk disclosure in palm oil companies. These findings suggest that auditor competence plays an important role in enhancing transparency and improving the quality of information related to climate change risks disclosed in corporate reports.